ANALYSIS OF THE USE OF LANGUAGE VARIETIES BY TRADERS IN BUYING AND SELLING TRANSACTIONS - Alfianor, Rahmayanti, Husni Mubarak (STKIP Paris Barantai, 2025)
The purpose of this study is to describe the use of language varieties of traders reviewed through Sociolinguistic studies. This study uses. The method used in this study is descriptive qualitative by presenting studies and analysis of data directly related between researchers and informants who have been collected and selected data sources and analysis based on the data obtained. The instruments used by researchers are observation and documentation. Based on the results of the study obtained, there are six language varieties that can occur in the Geronggang Village market, namely, standard variety, business variety, casual variety, dialect variety, non-standard variety, and familiar variety. The factors that influence the language variety of traders in this study are situational factors, age factors, familiarity factors and sociocultural factors. Keywords: language variety, traders, buying and selling transactions